Students' Learning Difficulties Review from Mathematics Problem-Solving Ability in Third-Grade Elementary School - Dwi Sulistyani; Ervina Eka Subekti; M.Yusuf Setia Wardana (Universitas Pendidikan Ganesha, 2021)
Difficulty in the calculation process. It has an impact on low mathematics learning outcomes for students. This study aims to analyze students' learning difficulties in terms of mathematical problem-solving abilities in grade III elementary school fractions. This type of research is descriptive qualitative research. The subjects taken were six students—data obtained through interviews, tests, and documentation. The instrument used to analyze the data is a questionnaire. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The study results are that students have a score on the aspect of understanding the problem of 50 (33.3%) in the medium difficulty category. The planning aspect has a score of 34 (22.60%) (great difficulty). Implementing the plan has a score of 95 (63.30%) (low difficulty). The re-checking aspect has a score of 98 (65.30%), which is in the low difficulty category. The difficulty is due to the lack of understanding of the questions, errors in determining the correct strategy to solve the problems and difficulties in the calculation process, and the child's low grasping power.